Cardiac Function Index as a Possible Target Parameter Hemodynamic Correction in Abdominal Sepsis (Pilot Study) - S. A. Rautbart; I. N. Tyurin; A. A. Alexandrovskiy; I. A. Kozlov (Общая реаниматология, 2021)
Aim of the study: to determine the predictive value of central hemodynamic parameters in relation to mortality and evaluate their potential acceptability for goal-directed therapy during days 1-4 of treatment in patients with sepsis.Material and methods. The results of investigation and treatment of 62 patients aged 50.9±2.13 years with abdominal sepsis were analyzed. The patient severity on admission to the intensive care unit was 13 [10-15] on the APACHE II scale, 8 [6.75-9.25] on the SOFA scale. Lethal outcome 15.6±1.4 days after admission occurred in 19 (31%) patients. Central hemodynamic parameters were studied by transpulmonary thermodilution according to the standard technique. Infusions and administration of sympathomimetic drugs were performed according to Sepsis-3 guidelines. Statistical analysis was performed using logistic regression and ROC analysis.Results. The median values of the main circulatory parameters during days 1-4 of sepsis treatment were within normal ranges. Cardiac index, afterload-related cardiac performance, global cardiac ejection fraction and cardiac function index were predictors of mortality at all stages of treatment. However, the first three parameters did not provide either sufficient model quality at the study stages or a stable cutoff value with acceptable sensitivity and specificity. The cardiac function index maintained good model quality (area under the ROC curve 0.708-0.753) and a stable cutoff value (≤5.75 to ≤5.81 min-1) with acceptable and balanced sensitivity and specificity of about 70% at all study stages.Conclusion. The cardiac index, afterload cardiac performance, global cardiac ejection fraction and cardiac function index during days 1-4 of intensive care of sepsis are predictors of lethal outcome. At the same time, only the cardiac function index maintains good model quality and consistent cut-off point value with acceptable sensitivity and specificity at all stages of the study. The feasibility of using the cardiac function index as one of the parameters of goal-directed therapy aimed at cardiovascular function improvement in sepsis needs further investigation.